Personnel Identification and Early Warning System for Comprehensive Excavation Equipment - WANG Tingming, LI Pengpeng, SUN Baohai, CAO Lianmin (Meikuang Anquan, 2020)
To solve the safety problem of pedestrian accident caused by the movement of the rear conveyor in the blind area of the field of vision of the comprehensive driving equipment in underground coal mine, based on infrared imaging and image processing technology, this paper designs a personnel identification and early warning system which is suitable for underground integrated excavation equipment. The system adopts modular design and integrated package, and carries out application test and structural optimization on the continuous shearer. The test proves that the system has high identification accuracy and rapid response, and can accurately identify pedestrians in the dangerous area of the integrated excavation equipment, and realize early warning of personnel within 2 m outside the danger area and shutdown operation within 1 m and 1 s.